What are local issues? The problem of the local review of research - Wainwright, P. (Journal of medical ethics, 2004)
Local review of research by ethics committees in the UK has long been held to be an important right of the local research ethics committee and, even with the introduction of the European Clinical Trials Directive, the governance arrangements for research ethics committees continue to allow for local review of multicentre studies. There is no requirement for local review in either the European Union directive or in the guidelines on good clinical practice, and there is little evidence of it anywhere else in Europe. The idea that there can be “local”, as opposed to “central” ethical issues in research is an interesting one, which raises important issues about the nature of research ethics and ethical review. The aim of this paper is to argue that there are no such things as local issues in research ethics, and suggest that those questions currently addressed as local issues properly belong within the research governance framework.